Edukasi bagi pengelola bank sampah di Kabupaten Sleman mengenai manfaat manajemen dan pencatatan keuangan bank sampah - Reni Anggraini; YFM Gien Agustinawansari; Theodorus Sutadi; Trisnawati Rahayu; Yusef Widya Karsana (Universitas Sanata Dharma, 2026)
This Community Service Program (PKM) aims to educate waste bank managers in Sleman Regency about the importance of financial management and record-keeping. The community service program (PKM) was held at the Pendopo of the Sleman Regent's Official Residence. The meeting was attended by 57 waste bank managers in Sleman Regency, who are members of the Independent Waste Management Network (JPSM). The service was delivered through education on managing a waste bank from managerial and financial perspectives. Next, a Q&A session was held with the participants to discuss their experiences with recording and managing their finances. The findings showed that they still face many challenges in human resources and financial management because most of them work voluntarily. The discussion also revealed that members often overlook administrative procedures, for example, forgetting to bring their waste savings book, making proper recording difficult. In addition, regarding financial management, not all members make good financial reports, as they still see it as a time-consuming task. Most participants need a technology-based recording method to complete the recording process more quickly and accurately.